2017
DOI: 10.1002/ijc.30759
|View full text |Cite
|
Sign up to set email alerts
|

Patient monitoring through liquid biopsies using circulating tumor DNA

Abstract: Tumors release components such as circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), and tumor-derived extracellular vesicles into the circulation. Multiple studies have demonstrated that molecular information about tumors and metastases can be extracted from these factors, which are therefore frequently referred to as "liquid biopsies." Liquid biopsies allow the longitudinal monitoring of tumor genomes non-invasively and may hence ensure that patients receive appropriate treatments that target the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 82 publications
(172 reference statements)
1
43
0
1
Order By: Relevance
“…In the present study, this was exemplified by patient #35153 where some of the emerging somatic alterations, such as loss of PTEN or RB1 and the novel gain of 20q13, which harbors the AURKA gene, have been reported as frequent changes in t-NEPC 5054 and represent a potential therapeutic target 55 . AR antagonism may induce lineage alterations and thus promote enhanced lineage plasticity 19, 5254, 56 , as previously reported by us and others 11, 19 . Furthermore, we describe several cases in which genomic alterations evolve with disease progression, but at present it is unclear whether these are associated with response/resistance to abiraterone/enzalutamide.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, this was exemplified by patient #35153 where some of the emerging somatic alterations, such as loss of PTEN or RB1 and the novel gain of 20q13, which harbors the AURKA gene, have been reported as frequent changes in t-NEPC 5054 and represent a potential therapeutic target 55 . AR antagonism may induce lineage alterations and thus promote enhanced lineage plasticity 19, 5254, 56 , as previously reported by us and others 11, 19 . Furthermore, we describe several cases in which genomic alterations evolve with disease progression, but at present it is unclear whether these are associated with response/resistance to abiraterone/enzalutamide.…”
Section: Discussionsupporting
confidence: 78%
“…Molecular biomarkers related to drug sensitivity and resistance were detected in blood, suggesting that tumor-derived variations in blood may be more clinically relevant than those that are blood-specific. Although many articles have verified the clinical applicability of tumor-derived variations in diverse tumor types (Abbosh et al, 2017;Esposito et al, 2014;Ulz et al, 2017), our study is the first to confirm the utility of tumor-derived variations in blood using basic sequencing analysis. We predict that additional biological and clinical implications of ctDNA profiling will be revealed in further studies with larger populations.…”
Section: Discussionmentioning
confidence: 73%
“…To this end, we think that newer approaches such as assay for transposase-accessible chromatin using sequencing (ATAC-seq) (Buenrostro et al 2013) may provide open chromatin data that could be used by our approach. On the other hand, Ulz et al (2017) demonstrated the potential of plasma DNA coverage pattern analysis in inferring the expression of genes thus revealing the tissue origin of tumors in cancer patients. However, the authors estimated that a 75% tumor DNA fraction in the plasma might be required for this purpose (Ulz et al 2017), which was unlikely to be seen in most clinical cases.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ulz et al (2017) demonstrated the potential of plasma DNA coverage pattern analysis in inferring the expression of genes thus revealing the tissue origin of tumors in cancer patients. However, the authors estimated that a 75% tumor DNA fraction in the plasma might be required for this purpose (Ulz et al 2017), which was unlikely to be seen in most clinical cases. In contrast, our approach could work on cases with a much lower fraction of DNA from the tissue www.genome.org…”
Section: Discussionmentioning
confidence: 99%